PERAN WAKAF PRODUKTIF DALAM MENDUKUNG KESEHATAN DI MASA PANDEMI PADA WAKAF MANDIRI SURABAYA - Ainnur, Ainnur Kholifah; Suryaningsih, Sri Abidah (Universitas Negeri Surabaya, 2023)
Limited access to finance and health is a major obstacle for the poor so that related to health problems during a pandemic, Islam has a solution through Islamic philanthropic institutions, one of which is waqf. Therefore, community contribution is needed through waqf. This is because in Islamic history the issue of waqf in the health sector has motivated many parties in all Muslim countries to reactivate waqf in the health sector. This article aims to find out the role of productive waqf in supporting health during a pandemic at Waqf Mandiri Surabaya. The method used in this study is a qualitative method with a qualitative approach that is descriptive in which the author describes the Health waqf during a pandemic. The results of research on the role of productive waqf show that there is good cooperation between ZIS institutions and waqf institutions during a pandemic in supporting health. The distribution of waqf in the health sector has an impact on teachers or employees seeking treatment through health clinics. Also, the role of productive waqf has been implemented for medical staff at health centers and health workers at hospitals by providing multivitamins, personal protective equipment, and so on. Then, the Mandiri Waqf Health UKS was established with the Waqf and when students were sick they could seek free medical treatment at the UKS with medical devices which were also supported by ZIS funds.